(untitled) (Bangladesh Journal of Botany, 2025)
Identifying and utilizing the superior storage potential of seeds in landraces with distinctive characteristics are crucial to withstand adverse environmental changes, seed conservation and breed a new variety. As a result, an experiment was conducted to assess the storage potential of 17 important rice landraces. The results showed that the seeds of all the landraces have maintained maximum germination (>80%) for 12 months under ambient condition except Thulasi vasanai, which retained required viability upto 11 months only. Also, Karuppu kavuni has excelled in seed storage and recoded 82% germination at 20 months and the landraces Idly (88%) and Navara (86%) had greater germination up to 18 months. Thus, Karuppu kavuni, Idly and Navara are the superior landraces remarkably with good storage potential that could be suggested for the crop improvement programme. Bangladesh J. Bot. 54(2): 397-401, 2025 (June)